Systematic literature review of humble leadership from article journal in 2012-2024 - Ervianto, Luthvi Rachman; Syah, Tantri Yanuar Rahmat; Meria, Lista; Safuan, Safuan (International Journal of Innovative Research and Scientific Studies, 2025)
Dynamic organizations are of great interest to study because they are increasingly engaging. A successful organization is one that is dynamic and developing, has a global perspective, and is always changing. These conditions all depend on its leader. The purpose of the study is to provide a concept of humility in leadership that differs from traditional leadership styles, which often emphasize authority and power. The methodology used is based on the Systematic Literature Review (SLR) related to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), which involves several important steps aimed at ensuring transparency, reproducibility, and high-quality results. The result is that the most cited article is "Modeling the Way of Growth: An Inductive Examination of the Behavior, Likelihood, and Outcomes of Humble Leaders." This article is significantly more cited than other articles, indicating that it has a great influence on research regarding humble leadership. Articles published earlier tend to have more citations, indicating that research on humble leadership is relatively new and continues to grow. The conclusion of this systematization is that humble leadership has a positive influence and impact on various aspects, including individuals, teams, and organizations.